Discriminating scheelite deposit types using interpretable ensemble learning: A case study from the Xuefengshan Au-Sb-W belt, South China - Xiao-Ran Zhou; Qi-Liang Liu; Biao Liu; Jing-Hua Wu; Safiyanu Muhammad Elatikpo; Fei Deng; Shiwei Cui (Journal of Geochemical Exploration, 2026)

Dynamic Early Warning Model for Coal Spontaneous Combustion Based on Machine Learning - Gang Bai; Ran Liang; Wei Wang; Yun Qi; Xiaowen Zhang; Xueming Li; Xun Zhang (Natural Resources Research, 2026)

Decoupling fluorescence attenuation from structural degradation of carbon dots in soil leachates using bispectral monitoring - Qi Wang; Hao-Ran Song; Jun-Wei Liang; Wen-Hao Su; Yankun Peng (Journal of Hazardous Materials, 2026)

Exceptionally cost-effective and easily reusable Fe3O4-doped SnO2-Sb electrode with enhanced OH generation for degradation of typical refractory organic pollutants in wastewater - Zhirui Chen; Qi Wang; Xuejiao Ran; Rui Wang; Mingming Wang; Liang Feng; Feiyun Sun (Desalination, 2026)

Posttranslational regulation of TOR kinase activity controls resource allocation between plant growth and immunity in Arabidopsis - Jianwei Li; Ran Wang; Chenying Li; Xijie Guo; Qinghong Li; Zhixuan Wu; Shanshan Zeng; Fan Qi; Yuchen Wang; Zhiyi Jia; Weiwei Yu; Zeming Huang; et al. (Molecular Plant, 2026)

Responses of carbon monoxide photoproduction in surface seawater to environmental changes under simulated solar radiation - Xuan Ji; Ming-Liang Zhao; Yi-Ran Jia; Cai-Jie Zhang; Qi-Mei Du; Jing Zhang; Gui-Peng Yang (Marine Chemistry, 2026)

Curcumin-mediated photodynamic action disturbs TOM70-depedent MIC60 import to damage mitonchondria against breast cancer - Xiang-Yi Zhao; Min Yan; Liang Zheng; Chang-Long Gou; Qi Huang; Liu-Gen Li; Xin-Ran Yu; Jing-Yu Lu; Cui Hu; Si-Han Zhang; Cunqing Kong; Fan Leng; et al. (Journal of Photochemistry and Photobiology B: Biology, 2026)

Bifidobacterium animalis subsp. Lactis A6 alleviates comorbid constipation and depression by rebalancing tryptophan metabolism - Jian Wang; Yimei Ren; Juan Chen; Shanbin Chen; Xiaoxia Li; Jianwen Chen; Xifan Wang; Lijun Li; Liang Zhao; Yixuan Li; Qi Zhang; Wei Xiong; et al. (Science Bulletin, 2025)

Latest progress based on doped-TiO2 photocatalysis materials: Fabrication and applications - Xiao-Ni Qi; Ya-Qi Zhu; Hui Yuan; Zi-Xuan Xu; Hao-Ran Guo; Zhen-Liang Li (Journal of Water Process Engineering, 2025)

Bioremediation strategies for hexavalent chromium: Development and safety assessment of recombinant Escherichia coli strain 3458 - Yeting Weng; Qiuying An; Dongbei Guo; Ningjing Gan; Weijie Zeng; Wanting You; Zhangye Ma; Jiayan Qi; Zhiyu Zhang; Lirong Zhang; Mufeng Liang; Hongyuan Zeng; et al. (Journal of Environmental Management, 2025)

Independent and joint effects of volatile organic compounds on pulmonary function in U.S. adults from NHANES: the mediating role of platelet-to-lymphocyte ratio - Yan-Fei Wei; Hao-Wen Chen; Kuan Liu; Shi-Ao Wang; Wei-Dong Fan; Zhan-Hui Shao; Bi-Fei Cao; Yong-Qi Liang; Zheng-Yun Xu; Kai-Yue Liao; Zi-Xuan Zhao; Lu-Rong Yang; et al. (Environmental Pollution, 2025)

Schistosoma japonicum cystatin attenuated CLP-induced sepsis in mice though inducing tolerogenic dendritic cells and regulatory T cells - Yi-Xiang Wang; Yi-Dan Ma; Hui-Hui Li; Wen-Juan Duo; Qi-Wang Jin; Kai-Jun Zhou; Yan-Ran Gao; Jun-Nan He; Yu-Jie Xie; Liang Chu; Xiao-Di Yang (Comparative Immunology, Microbiology and Infectious Diseases, 2025)

Antimicrobial p -terphenyl derivatives from the deep-sea cold seep-derived fungus Aspergillus candidus - Yi-Yi Liu; Jing-Ya Shi; Qi-Ran Liang; Guang-Ying Chen; Hai-Xin Chen; Zhuang Han; Xu-Hua Nong (Natural Product Research, 2025)

A comprehensive omics resource and genetic tools for functional genomics research and genetic improvement of sorghum - Chengxuan Chen; Fengyong Ge; Huilong Du; Yuanchang Sun; Yi Sui; Sanyuan Tang; Zhengwei Shen; Xuefeng Li; Huili Zhang; Cuo Mei; Peng Xie; Chao Li; et al. (Molecular Plant, 2025)

Selective preparation of aromatic compounds from catalytic pyrolysis polyester coating over Ni, Mo and Co metal modified ZSM-5 - Zhen-Qiang Yu; Yao-Xin Xiao; Dong Liang; Che Zhao; Zhen Huang; Gang-Qi Cheng; Rui Shan; Hao-Ran Yuan; Yong Chen (Journal of Environmental Chemical Engineering, 2025)

Tracking sustainable development in mining towns: A novel framework integrating socioeconomic and eco-environmental perspectives through coupling coordination degree - Xiaofei Sun; Huaiyong Shao; Shuneng Liang; Yingzhi Zhou; Xiaoai Dai; Meng Liu; Ran Tao; Zhiheng Guo; Qi Xin (Environmental Impact Assessment Review, 2024)

B/N modified carbon nanofiber mesh covered with layered double hydroxide for large current overall water splitting - Ji Qi; Chunqi Zhu; Jianing Hu; Shuai Ran; Tauqeer Ahmad; Siraj Ullah; Lixu Chen; Yi Chen; Yuqing Xia; Xue Sun; Chuang Li; Xiao Chen; et al. (Fuel, 2024)

C-Phycocyanin improves the quality of goat oocytes after in vitro maturation and vitrification - Xing-Yue Wang; Yang Gao; Hao-Ran Liu; Teng Wang; Meng-Lei Feng; Fang-Rui Xue; Kang Ding; Qi Yang; Zhao-Yu Jiang; Dui Sun; Chun-Ru Song; Xiao-Jie Zhang; et al. (Theriogenology, 2024)

Uptake, subcellular distribution, and fate of tetracycline in two wetland plants supplemented with microbial agents: Effect and mechanism - Jie Zhong; Hang Wei; Jian-Xiong Xie; Yu-Hui Wu; Bing Tang; Qi Zou; Peng-Ran Guo; Zhi-Liang Chen (Journal of Environmental Management, 2024)

Controls on apatite compositional variations in magmatic rocks: A case study of Mesozoic mafic–felsic intrusions from the eastern North China Craton - Xiang-Yu Yan; De-Bin Yang; Wen-Liang Xu; Yi-Kang Quan; An-Qi Wang; Le-Ran Hao (Journal of Asian Earth Sciences, 2024)

Recycled crustal components in the depleted mantle source: Evidence from Early Cretaceous mafic rocks in the southern margin of the North China Craton - An-Qi Wang; De-Bin Yang; Wen-Liang Xu; Hao-Tian Yang; Yi-Kang Quan; Xiang-Yu Yan; Le-Ran Hao; Feng Wang (Lithos, 2024)

Identification of metasomatic components in lithospheric mantle under multiple tectonic regimes: Insights from Early Cretaceous mafic rocks in the northeastern North China Craton - Xiang-Yu Yan; De-Bin Yang; Wen-Liang Xu; Yi-Kang Quan; An-Qi Wang; Le-Ran Hao; Feng Wang (Lithos, 2023)

Pulsed counterclockwise rotation of the southwestern Sichuan Basin in response to the India-Asia convergence during 128-42 Ma - Qi Shen; Chun-Sheng Jin; Wen-Tian Liang; Chuan-Zhi Li; Hui-Hui Yang; Ya-Zhou Ran; Xuan He; Guan-Zuo Wu; Kai Jiang; Jian-Gang Li; Peng Han; Si-Hua Yuan (Earth and Planetary Science Letters, 2023)

Responses of Rice and Related Cadmium Transporter Genes to the Passivating Microbial Agent MBLHAP - Xiaoxi Zeng; Song Ran; Xiaoran Shen; Cheng Zhang; Hong Xu; Yilin Qi; Xinping Ren; Liang Ma (Current Microbiology, 2023)

Life cycle assessment of integrated bioelectrochemical-constructed wetland system: environmental sustainability and economic feasibility evaluation - Ying-Ke Fang; Hong-Cheng Wang; Pan-Hao Fang; Bin Liang; Kun Zheng; Qi Sun; Xi-Qi Li; Ran Zeng; Ai-Jie Wang (Resources, Conservation and Recycling, 2023)

Apatite geochemistry from mafic rocks in the northeastern North China Craton: New insights into petrogenesis - Xiang-Yu Yan; De-Bin Yang; Wen-Liang Xu; Yi-Kang Quan; An-Qi Wang; Le-Ran Hao; Hao-Tian Yang; Feng Wang (Lithos, 2023)

Investigation on long-term progressive deformation of engineering slope based on comprehensive monitoring - Shi-shu Zhang; Song-feng Guo; Sheng-wen Qi; Feng-jiao Tang; Jin-shan Hu; Xiao-ping Zhao; Cong-yan Ran; Xin Wang; Yu Zou; Xiao-lin Huang; Bo-wen Zheng; Ning Liang (Journal of Mountain Science, 2022)

Ecological adaptation shaped the genetic structure of homoploid ferns against strong dispersal capacity - Si‐Qi Liang; Xian‐Chun Zhang; Ran Wei (Molecular Ecology, 2022)
The formation of spatial genetic structure with the presence of extensive gene flow, an evolutionary force which is generally expected to eliminate population‐specific variation and maintain genetic homogeneity, remains poorly understood. Homosporous ferns, which spread by spores through wind and possess long distance dispersal capacity, provide an ideal system to investigate such a process. Here, using a homoploid fern lineage, the Athyrium sinense complex, we used reduced‐representation genomic data to examine spatial genetic structure and explored potential driving forces including geographical distance, environment, climatic history and external dispersal constraints. Our findings showed a clear north‐south divergence at the genetic, morphological and ecological levels between both sides of 35°N in East Asia. Fluctuant and heterogeneous climatic condition was demonstrated to play a crucial role during the formation of the divergence. Our results suggested that this lineage was able to migrate southward and colonize new habitat as a result of the Quaternary climatic fluctuation. Furthermore, the present genetic structure is attributed to adaptation to heterogeneous environments, especially temperature difference. In addition to ecological adaptation, we found clues showing that canopy density, wind direction as well as habitat continuity were all likely to constrain the effect of gene flow. These results demonstrated a diversification process without ploidy changes in ferns providing new insights for our present knowledge on ferns’ spatio‐temporal evolutionary pattern. In particular, our study highlights the influence of environmental heterogeneity in driving genetic divergence against strong dispersal capacity.

Incubation of sperm heads impairs fertilization and early embryo development following intracytoplasmic sperm injection (ICSI) by decreasing oocyte activation in mice - Hui Long; Sheng-Sheng Lu; Yan-Ping Kuang; Zhi-Guang Yan; Hong-Xing Liang; Sha Yu; Wei-Ran Chai; Zheng Yan; Qi-Feng Lyu (Biotechnology Letters, 2013)